Women's Family and Employment Life Courses Across Twentieth-Century Europe: The Role of Policies and Norms - Hannah Zagel; Zachary Van Winkle (Social Politics: International Studies in Gender, State & Society, 2022)
This article examines longitudinal patterns of work–family reconciliation across Europe and whether the influence of defamilizing policies on those patterns is contingent on the normative context. Data from the Survey of Health, Ageing and Retirement and sequence analysis are used to reconstruct and analyze women's family and employment life courses from age fifteen to fifty years, born in the period between 1924 and 1966 from fourteen countries. Historic family policy data and gender attitudes collected in the International Social Survey Programme are included in multinomial regressions. Results suggest that defamilization and gender egalitarianism increase the labor market attachment of women with traditional family life courses independently.
Keywords: 320